(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, the experiences of foreign countries on energy saving, which are relevant today, were considered. Acquaintance with the experience of implementing energy conservation policies in developed countries. The reasons for using steam-gas technologies are explained.